FACTORS AFFECTING THE SELECTION OF TRANSPORT SERVICES CASE STUDY OF THE TRANSPORTATION COMPANY SERVICE - Chuchuttaworn, Chuleekorn (RMUTT Global Business and Economics Review, 2022)
The objectives of this study were 1) To study the user’s use of Transport service 2) to study the factors that affect the choice Transport Services. The researchers collected questionnaire data using survey techniques based on Revealed Preference Method (RP). The size of the population-aware sample is small, determining the size of the sample by using Krejcie and Mrogan. The sample size was 200 people from 371 people of users toward the case study of Transportation Services, in the Khlong Luang area of Pathum Thani province. The researchers used Chi-Square Test of Independence determines whether there is an association between categorical variables, finding that 1) factors that influenced the choice of shipping companies in all of them. The user has a very high level of satisfaction. Income demographic factors Correlated with the behavior of freight service users The area chosen to use the transportation service has the most frequent cargo. Satisfied shipping time When there is a need for the service, and if there is another transportation service available, Statistically significant at the level of 0.05 occupational demographic factors. Correlation to the behavior of freight service users in the most frequently used area transport factors. Statistically significant at level 0.05 2) factors affecting the choice of freight services. It has no relation to the behavior of freight service users in all factors.